MARKETING STRATEGY THROUGH SOCIAL MEDIA AND STUDENT BUYING INTEREST - Zaman, Komarun (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
The purpose of this study is to know the relationship between marketing communication strategy of Brodo footwear on Instagram and willingness to buy of students in (STIE Pemuda). Using stratified proportional and purposive sampling techniques, the sample of this research is 95 students of STIE pemuda attended in year 202 and 2013. Data collecting is done by using two techniques, library research and field research. Data collecting is done by distributing questionaires consist of 20 closed-ended questions. Data analysis is done by using single and cross table analysis as well as hypothesis test using Spearman (Spearman's Rho Rank- Order Correlation) formula. The result shows that there is a certain and low relationship between marketing strategy of Brodo Footwear and the willingness to buy among students of (STIE Pemuda).